Revisiting building block ordering of long-period stacking ordered structures in Mg–Y–Al alloys. (15th June 2018) - Zhang, H.; Liu, C.Q.; Zhu, Y.M.; Chen, H.W.; Bourgeois, L.; Nie, J.F.
Abstract: Long-period stacking-ordered (LPSO) structures in Mg alloys have received considerable attention in the past decade due to their unique crystallographic features, but their precise structures are still not fully established. In this work, the 18R LPSO structure in two Mg–Y–Al alloys, in both cast and homogenized conditions, is systematically investigated using atomic-scale high-angle annular dark-field scanning transmission electron microscopy and density functional theory. Our observations reveal that there exist at least four types of building clusters—three of them being metastable and hitherto unreported—in the 18R structure in the as-cast condition. Each of the four types of building clusters comprises three Al–Y cubes that are connected by one Mg–Y cube. After annealing at 530–550 °C for 47–48 h, the three metastable building clusters transform to a stable configuration that is characterized by the Al6 Y8 L12 -type building cluster. These transformations are validated by first-principles calculations. Based on the experimental observations and computational results, the evolution of the building clusters in the 18R structure is elaborated. Graphical abstract: Image 1